The Effect of Trade Liberalization on Marriage and Fertility: Evidence from Indian Census - Shruti Sengupta; Mehtabul Azam (Institute of Labor Economics (IZA), 2022)
Using a district-level panel constructed from five waves of decennial Indian censuses covering 1971-2011, we examine the medium-term (1991-2001) and long-term (1991-2011) impacts of the 1991 Indian trade liberalization on marriage and fertility rates among young women aged 15-34 years. We exploit the fact that countrywide tariff reductions varied across industries creating exogenous local labor market shocks based on the initial employment composition of the district. We find heterogeneous results across urban and rural areas. We find that urban areas of the districts that experienced larger tariff cuts experienced relative increase in marriage rate compared to the districts that experienced smaller tariff cuts. Moreover, tariff cuts positively affect the workforce participation among both young men and women in urban areas. However, there is no impact of tariff cuts on marriage rate or workforce participation among young for rural areas. In contrast, tariff cuts reduced fertility rate mostly in rural areas.
Keywords: J12; J13; O12; 330; marriage; fertility; trade liberalization